Determinación de la patogenicidad de Beauveria bassiana sobre la Gualpa (Rhynchophorus palmarum L.), en condiciones de laboratorio. - Guevara Loor, Deivy Gabriel (2018)
The "Gualpa", Rhynchophorus palmarum L. is an insect of economic importance in the cultivation of oil palm and coconut palm in Latin America and the Caribbean. This coleoptera is a very important pest in the plantations of African palm or oil palm and in the coconut trees because it is the main vector of the disease known as the Red Ring - Shortleaf (RA). The use of entomopathogenic fungi is an alternative that has been opening space in pest management programs, with the entomopathogenic fungus Beauveria bassiana as one of the main microorganisms for the biological control of insects. For this reason, the objective of determining the pathogenicity of the fungus Beauveria bassiana on the gualpa (R. palmarum L.), under laboratory conditions. The research was carried out in the microbiology laboratory of the State Technical University of Quevedo. In the experiment, live adults of Gualpa collected at the "San Javier" hacienda and a strain of Beavueria bassiana isolated from the black banana weevil, maintained in the bank of strains (CINCAE), were used. As relevant results it was obtained that all the concentrations of conidia of B. bassiana exerted an entomopathogenic (pathogenic) activity towards R. palmarum observing mycelial growth at 12 days after the inoculation and that the concentration 1 x 108 had the highest number of insects dead with 2, 7 and 9 individuals at 5, 10 and 15 days. In contrast to the concentrations 1 x 105, 1 x 106 and 1 x 107 that presented values between 1 and 2; 2 to 6 and 3 to 7 insects at 5, 10 and 15 days respectively.After the analysis and interpretation of the results, the following conclusions were obtained: The strain of the fungus B. bassiana was pathogenic on the gualpa in the different concentrations used, with 1 x 108 conidia/ml being the highest mortality in adults of the gualpa (R. palmarum L); the concentration 1 x 108 conidia/ml of B. bassiana caused the highest number of dead insects, presenting itself as the concentration of greatest efficacy in the biological control of the gualpa (R. palmarum L); the mean lethal concentration that reflected 50% of dead insects was 4.51 x 105 and in the mean lethal time it was determined at the concentration 1 x 108, as the one with the highest control in about 90% mortality of the gualpa insects ( R. palmarum L) in the least number of days within the study. Keywords: Gualpa, Rhynchophorus palmarum L, Beauveria bassiana